Dynamic Stability of an Elastic Rotating System: Shell-Disc-Shaft - P. Ruge; P. Senker (International Journal of Rotating Machinery)
This paper presents a methodology and some results on the dynamic stability of an elastic rotating system consisting of one- and twodimensional members. These parts may contain different kinds of unsymmetries: either from mass- or stiffness imperfections or from anisotropic especially hydrodynamic bearings. The equations of motion are formulated using virtual work and an Finite Element approach. Special attention is paid to a kinematically consistent coupling of the elastic shell and disc. The eigenvalue extraction is based upon the method of Lanczos including a modal reduction and a correction process in order to ensure true diagonal system matrices. Some typical results for a shaft-disc-shell system with different bearings and imperfections are presented in detail.